Montenegro Gender Diagnostic : Gaps in Endowments, Access to Economic Opportunities, and Agency - World Bank (Washington, DC, 2015)
In 2011, women and girls represented 50.6 percent of the total Montenegrin population (620,029 persons). Different aspects of gender inequality vary by region and ethnicity. The present World Bank country partnership strategy in Montenegro is based on two pillars that include supporting Montenegro s accession to the European Union (EU) through boosting institutions and competitiveness. The purpose of this report is to provide an overview of gender inequality in Montenegro. Using a number of data sources, gender differences in various outcomes are analyzed with the intention of highlighting gender inequalities in human wellbeing. Results are used to prioritize possible avenues for future research to better understand such inequalities and or suggest areas that require more focus from policymakers. This report operates under the premise that gender equality is both an issue of human rights and of critical economic consequence. In line with the world development report (WDR) 2012, the nomenclature of gender gaps in endowments, access to economic opportunities, and agency will be used to elaborate upon these arguments and their relevance to Montenegro. The findings of this diagnostic suggest that there are gender gaps in Montenegro, particularly in: (i) agency, although available data in this area is limited; (ii) access to economic opportunities; and (iii) human capital among some population subgroups. The structure of the report is as follows: section one gives introduction. Section two addresses gender disparities in endowments, including education, health, and assets. Section three presents disparities in economic opportunities in the forms of labor force participation, unemployment, employment and wages, and entrepreneurship. Section four focuses on agency and its implications for gender equality. Section five discusses relationships across issues and suggests areas for further research.